1989
DOI: 10.1007/bf01875608
|View full text |Cite
|
Sign up to set email alerts
|

Glycogenolytic action of glucagon-family peptides and epinephrine on catfish hepatocytes

Abstract: Glycogenolytic effects of salmon and mammalian glucagons, salmon glucagon-like peptide (GLP) and epinephrine were studied on liver cells isolated from catfish (Ictalurus melas). In spring and summer, salmo-glucagon (3×10(-10) to 3×10(-8) M) was more effective than its mammalian counterpart in the stimulation of glucose release and cAMP synthesis in hepatocytes. GLP was less potent as compared to both glucagons. γ-amylase activity was not affected by the treatment with either glucagon-family peptides or epineph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
1

Year Published

1990
1990
2003
2003

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 34 publications
1
9
1
Order By: Relevance
“…As expected (Brighenti et al 1987;Ottolenghi et al 1988Ottolenghi et al , 1989, these two hormones elevated CAMP levels and phosphorylase a activity in both pools of liver cells. They also decreased the glycogen content in hepatocytes and stimulated glucose release into the incubation medium.…”
Section: Discussionsupporting
confidence: 61%
“…As expected (Brighenti et al 1987;Ottolenghi et al 1988Ottolenghi et al , 1989, these two hormones elevated CAMP levels and phosphorylase a activity in both pools of liver cells. They also decreased the glycogen content in hepatocytes and stimulated glucose release into the incubation medium.…”
Section: Discussionsupporting
confidence: 61%
“…Our initial report on the absence of GLP-dependent cAMP increases in rainbow trout (Oncorhynchus mykiss) hepatocytes (Mommsen et al 1987), although confirmed for this species, had to be revised for other teleosts . Nevertheless, even in species where GLP-independent increases in cAMP were detected, a clear correlation between cAMP levels and biochemical output of the targetted cells was found wanting (Ottolenghi et al 1989;Mommsen and Moon 1990). Statistically significant increases in glycogenolytic or gluconeogenic rates, for instance, are observed at high picomolar concentrations of pGLPs, while increases in cAMP are not noted until hormone level exceed the low nanomolar level (Ottolenghi et al 1989;Mommsen and Moon 1990).…”
Section: Fishesmentioning
confidence: 86%
“…Nevertheless, even in species where GLP-independent increases in cAMP were detected, a clear correlation between cAMP levels and biochemical output of the targetted cells was found wanting (Ottolenghi et al 1989;Mommsen and Moon 1990). Statistically significant increases in glycogenolytic or gluconeogenic rates, for instance, are observed at high picomolar concentrations of pGLPs, while increases in cAMP are not noted until hormone level exceed the low nanomolar level (Ottolenghi et al 1989;Mommsen and Moon 1990). This discrepancy may even be exacerbated by the increased sensitivity of isolated fish cells maintained in perifusion.…”
Section: Fishesmentioning
confidence: 86%
“…The glycogenolytic action of catecholamines during stress is well established (Janssens and Waterman, 1988;Ottolenghi et al, 1989;Fabri et al, 1998) but there is also evidence that cortisol makes an important contribution to glycogen mobilization (Paxton et. al., 1984;Morales et al, 1990;Soengas et al, 1992bSoengas et al, , 1993Reubush and Heath, 1996).…”
Section: Discussionmentioning
confidence: 99%